2020
DOI: 10.3390/ijerph17072585
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Post-Traumatic Headache and Migraine: Pre-Clinical Comparisons

Abstract: Background: Oftentimes, persistent post traumatic headache (PPTH) and migraine are phenotypically similar and the only clinical feature that differentiate them is the presence of a mild or moderate traumatic brain injury (mTBI). The aim of this study is to describe the differences in brain area and in biochemical cascade after concussion and to define the efficacy and safety of treatments in use. Methods: Sources were chosen in according to the International Classification of Headache Disorder (ICHD) criteria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 64 publications
0
38
1
Order By: Relevance
“…Patients with persistent post-traumatic headache (PPTH) and patients with migraine have similar phenotypes (13). Migraine is the most common headache phenotype in patients with PPTH in clinic-based studies (4).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with persistent post-traumatic headache (PPTH) and patients with migraine have similar phenotypes (13). Migraine is the most common headache phenotype in patients with PPTH in clinic-based studies (4).…”
Section: Introductionmentioning
confidence: 99%
“…The main phenotype of PTH in patients with mTBI is consistent with that of migraine [ 5 , 6 ], and PTH commonly has characteristics similar to migraine. Thus, there are shared underlying neurochemical mechanisms between migraine and PTH [ 7 ]. Several studies have shown that various brain structures, such as the brainstem, central dopaminergic system and hypothalamus, are involved in the pathophysiology of migraine [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The debate on the relationship between mTBI, migraine, PTH, and PTSD has not yet found a definitive position [79,80]. It is unclear whether a head trauma triggers a biologically unique headache condition or whether the head pain mechanisms share migraine or tension-type pathways.…”
Section: Resultsmentioning
confidence: 99%